FRI0399 Joint Involvement in Patients Affected by Systemic Lupus Erythematosus: Association Between Power Doppler and Erosive Damage. (9th June 2015) - Ceccarelli, F.; Conti, F.; Perricone, C.; Iorgoveanu, V.; Spinelli, F.R.; Alessandri, C.; Valesini, G.; Iagnocco, A.
Abstract : Background: Joint involvement occurs in up to the 90% of patients with Systemic Lupus Erythematosus (SLE), with a wide spectrum of clinical features. Musculo-skeletal ultrasonography (US) has been successfully used in the assessment of inflammatory arthropathies. In particular, the presence of power Doppler (PD) signal, able to detect active inflammation through the identification of pathologically blood perfusion, has been considered a risk factor for the development of erosive damage in patients with Rheumatoid Arthritis (RA). Few studies focused on the evaluation of joint involvement in SLE by PDUS. This imaging technique confirmed its higher sensitivity compared with clinical evaluation. However, to our knowledge, the role of PDUS in SLE patients is still poorly investigated. Objectives: To evaluate the presence of PDUS synovitis and its associations with US-detected erosive damage at the level of hand and foot joints in SLE patients. Methods: One hundred and two consecutive SLE patients (M/F 1/101; mean age 44.5±11.6 years; mean disease duration 144.6±103.2 months) complaining joint involvement were enrolled. All patients underwent clinical evaluation, laboratory tests and bilateral high-resolution US of the metacarpophalangeal, (MCP), proximal interphalangeal (PIP), and metatarsophalangeal (MTP) joints. Joint effusion (JE), synovial hypertrophy (SH), PD and erosive damage were assessed with a dichotomous score (absence or presence) and then graded according to a semi-quantitative scale ranging from 0 to 3 (0=absent, 1=mild, 2=moderate and 3=severe). US inflammatory scores, calculated by adding the values given to each elementary lesion, were elaborated at the level of all single joints and at all joint groups (MTPs, MCPs, PIPs). Finally, a global score was obtained by adding the scores of all joint groups. Results: PDUS evaluation identified a median global US score of 16 (range 0-148). The median MCP, PIP and MTP joints scores were 2 (range 0-50), 1 (range 0-38) and 4 (range 0-38), respectively. The PIP score was significantly lower compared to MCP (P<0.0001) and MTP (P<0.0001). Nineteen over 102 (18.7%) of patients showed the presence of bone erosions. The presence of PD signal in at least one joint was identified in 25/102 (24.5%) SLE patients (median PD score=4, range 1-23). MCP joints showed the highest prevalence of PD signal. In particular, this US feature was registered in12.7% and 8.8% of the II and III MCP joints evaluated, respectively. A significant association between PD signal positivity and presence of erosive damage was found since 13 patients with PD positivity showed erosive damage (13/25; 52.1%) in at least one joint, compared with 6/77 (8.4%) patients without PD signal (P<0.0001). Moreover, when considering the US erosion score, patients with PD signal in at least one joint showed a significant higher erosive score compared with those without PD (median 1, range 0-9 versus median 0, range 0-7, P<0.0001). Conclusions: In the present study, we identified an association between PD and erosive damage in SLE patients with symptomatic joint involvement. Those results, similarly to previously reported data on RA, suggest a role of PD as a prognostic factor for aggressive and severe arthritis, which may be able to guide the physician in therapeutic options. Disclosure of Interest: None declared